Interpersonal Metafunction in Leonardo DiCaprio Speech - ASIH PRIHANDINI; ILYAS PERMANA PUTRA (Universitas Widyatama, 2019)
This study is aimed to analyze mood, modality and personal pronouns as the elements of interpersonal metafunction found in Leonardo DiCaprio